Spatial and Temporal Distribution of Microbes and Enzyme Activity in the Rumen of Buffaloes - Agarwal, Payal; Kala, Anju; Kamra, D N; Agarwal, Neeta; Chaudhary, L C (Indian Journal of Animal Nutrition, 2020)
Information about abundance of rumen microbes is a prerequisite to assess the fermentation in rumen during any dietary intervention. However, conventional techniques are not able to enumerate majority of microbes as majority of rumen microbes are uncultivable. Real time PCR (qPCR) has successfully been used for quantification of various rumen microbes like rumen cellulolytic bacteria, protozoa, fungi, methanogens etc. In this experiment, the whole rumen content (WRC) was squeezed to particulate matter (PM) and squeezed rumen liquor (SL), whereas, the fourth fraction, strained rumen liquor (SRL) of rumen content was obtained by filtering through a probe with double layer of muslin cloth.Â The population of total bacteria, fungi, Ruminococcus albus, R. flavefaciens, Fibrobacter succinogenes, total methanogens, Butyrivibrio fibrisolvens and protozoa were estimated in different fractions of rumen content at 0, 4 and 8 h post-feeding by real time PCR using specific primers. The numbers of these microbes were significantly (P<0.001) higher in WRC and PM as compared to SRL and RL. The activities of carboxymethylcellulase (CMCase), avicelase, amylase, xylanase, Î²-glucosidase and urease were significantly (P<0.05) higher in WRC and PM as compared to SRL and RL. The activities of CMCase and urease were higher (P<0.05) at 4 and 8 h post feeding, whereas, rest of the enzymes were not affected. There was no effect of time of sampling on the population of rumen microbes explored in this experiment. It appeared that WRC or PM fraction provided true picture of microbial and enzyme profiles responsible for fibre degradation in the rumen. The increase in enzyme activity at a particular time of sampling was not associated with population size of the specific microbes or specific activity of enzymes.